Contributions to the Automatic Restoration of Images from Scenes in Participating Media - Drews-Jr, Paulo L. J.; Nascimento, Erickson R.; Campos, Mario F. M. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2017: Anais do XXX Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2017.3459, 2017)
This work deals with the problem of image restoration of monocular images acquired in participating media, i.e. media that interfere with light propagation. Specifically, the proposed work focus on the automatic restoration of images acquired in underwater and foggy/hazy scenes. The proposed restoration process requires at least a pair of images as input and produces images in which the medium effects are attenuated and the visibility improved. Differently from previous works, our method does not need additional equipment or information. We proposed a new model-based approach by estimating the depth map and the attenuation coefficient. We performed experimental evaluation in real and simulated environments with significant improvement in the quality of the images.